Efecto de la inoculación multiespecie con Bacillus spp. y Paenibacillus polymyxa frente al manejo restrictivo de nutrientes sobre la sanidad y rendimiento en trigo (Triticum aestivum L.). - Jaramillo Gavidia, Suleny Sofia (2025)
Wheat crop (Triticum aestivum L.) plays a crucial role in global food security. However, Ecuador faces limited access to plant material with some level of tolerance to fungal diseases and poor nutrient management, which affects its yield. The objective of this research was to evaluate the effect of multi-species inoculation with Bacillus spp. and Paenibacillus polymyxa, along with different levels of fertilization, on wheat health and yield in the Bolívar province. A randomized complete block design (RCBD) with a 2 × 5 factorial arrangement and three replicates was used. The results showed better plant height (PH), tiller number (TN), and yield (YLD) with the application of 100% fertilizer combined with inoculation (T6 y T7). In terms of plant health, adding 75 and 100% fertilizer reduced the severity of leaf spot (LS), although no effect of inoculation was observed on this variable. However, full fertilization without inoculation promoted rust severity, reaching 59.08%. The economic analysis indicated that the treatment without inoculation and without fertilization (T5) was the most profitable, but inoculation contributed to disease reduction during developmental stages. The multi-species combination analyzed in this study demonstrated that, with proper nutrient management, it could be a promising strategy to improve wheat yield while considering the variable costs associated with the treatments.